Increasing Social Entrepreneurship in Digital Media for Individuals With Lupus and Low Vision - Firmansyah, Firmansyah; Permatasari, Andalusia Neneng; Satriani, Arba'iyah; Kusumalestari, Ratri Rizki; Kurnia, Septiawan Santana (UI Scholars Hub, 2024)
This paper discusses the development of social entrepreneurship empowerment for individuals with lupus and limitations in vision through Asset-Based Community Development (ABCD), defined based on identifying their substantial aspects. After defining the characteristics of conditions of individuals with disadvantaged health, such as lupus and low vision, an ABCD approach is developed. The approach is planned within the framework of business development using digital media, carrying out five key steps—Discovery, Dream, Design, Define, and Destiny. It is argued that the ABCD concept can be effective in the continuity of the empowerment process, particularly in helping individuals with health inequalities. This study took place in collaboration with an NGO, Syamsi Dhuha Foundation, which aims to assist individuals with lupus and low vision to better participate in community life. The community program views social entrepreneurship as an entry point, where they are introduced to the concept of business strategy. Quantitative and qualitative studies are conducted to examine the program’s effectiveness. A descriptive statistic is employed to see the changes in the condition of the participants, which suggests that such programs have a significant contribution in providing insights. Meanwhile, the intensive discussion with the participants helps them identify potentials and strategies in entrepreneurship in digital marketing based on five key steps, i.e., looking for a strategy so that better user interface and experience in digital maneuvering for individuals with impaired health conditions, such as lupus and low-vision, can be developed. It is also demonstrated that continuous assistance can effectively strengthen the empowerment process, providing a more appropriate and meaningful strategy for individuals with disadvantaged health conditions.